Analyzing Challenges for the Implementation of E-Government in Municipalities within Kathmandu Valley - Dhonju, Ganesh Ram; Shakya, Subarna (Journal of Science and Engineering, 2019)
Over the past decade, rapid progress in ICT has encouraged governments to incorporate new technology into their national development strategies. With the growing demands of citizens and changing global rules and regulations, governments are under pressure to deliver quality services at right time. E-government has recently emerged in Nepal that‟s why so many issues remain problematic for initiation e-services in local government. The current stages of municipalities within Kathmandu Valley were investigated by using four stage e-government maturity model (information, interaction, transaction, integration). An understanding of the current status of e-government in local government can help policy makers in the country pursue development of the public sector organizations on the one hand, and would be of importance for Nepal's economic future success on the other. Identifying the precise problem is important in order to overcome the inherent challenges. Valuable primary data is collected from questionnaire survey and content analysis. Different challenges regarding initiation of e-based services in municipalities are categories into Financial, Human, Organizational, Technical and Legal & other challenges. The current status of e-based services delivery initiatives in Municipalities and problematic challenges in implementation of e-based services initiatives were being investigated. Lack of strategic plans, change management, budget constraint, weak infrastructure, literacy, lack of construction knowledge, lacks of leadership supports, security and privacy are found to be the most problematic challenges regarding implementation of e-service in municipalities.